Advances in the research of sulfur dioxide and pulmonary hypertension - Liu, Xin; Zhou, He; Zhang, Hongsheng; Jin, Hongfang; He, Yan (Frontiers in Pharmacology, 2023)
Pulmonary hypertension (PH) is a fatal disease caused by progressive pulmonary vascular remodeling (PVR). Currently, the mechanisms underlying the occurrence and progression of PVR remain unclear, and effective therapeutic approaches to reverse PVR and PH are lacking. Since the beginning of the 21st century, the endogenous sulfur dioxide (SO2)/aspartate transaminase system has emerged as a novel research focus in the fields of PH and PVR. As a gaseous signaling molecule, SO2 metabolism is tightly regulated in the pulmonary vasculature and is associated with the development of PH as it is involved in the regulation of pathological and physiological activities, such as pulmonary vascular cellular inflammation, proliferation and collagen metabolism, to exert a protective effect against PH. In this review, we present an overview of the studies conducted to date that have provided a theoretical basis for the development of SO2-related drug to inhibit or reverse PVR and effectively treat PH-related diseases.